Evaluación de métodos de concentración y purificación de Giardia spp. a partir de muestras coprológicas - Tarqui Terrones, Kathia (2019)
The aim of this study was to compare different methods of concentration to recover the largest number of Giardia spp. cysts from coprological samples. One hundred (100) samples from national reference hospitals were analyzed and four parasitological methods were applied: spontaneous tube sedimentation concentration (TSET), Faust, single-phase sucrose gradient, and two-phase sucrose gradient. The two-phase sucrose gradient method was found to achieve significantly better results in cyst concentration (121,903 cysts/ml) and amount of debris (6%), compared to Faust methods (35,355 cysts/ml), spontaneous tube sedimentation concentration (20,145 cysts/ml), and single-phase sucrose gradient (18,702 cysts/ml). It is concluded that the most effective method for the concentration and purification of Giardia spp. cysts from coprological samples is the two-phase sucrose gradient method, which would facilitate in vitro culture of Giardia spp.